PEMANFAATAN LIMBAH KULIT JENGKOL SEBAGAI BAHAN DASAR PEMBUATAN PUPUK ORGANIK PADA TANAMAN SAWI CAISIM (Brassica Juncea L.) - Fatimah Azzahra; Derita Ramai Durubanua; Sakira Putri Manurung; Kurnia Simbolon; Sri Muthia Hasan; Nina Novira (Percetakan Umi Toaha Makassar, 2026)
This study aims to utilize jengkol peel waste as a raw material for making liquid organic fertilizer (POC) and to analyze its effect on the growth of mustard greens (Brassica juncea L.). The study used a quasi-experimental design method consisting of two groups, namely the treatment group (using jengkol peel POC) and the control group (using chemical fertilizer). The study was conducted in Medan Tembung District, Deli Serdang Regency, for 45 days. The results showed that mustard greens given liquid organic fertilizer experienced increased growth. The t-test results showed a significance value <0.05 for all observation parameters, which means there was a significant difference in growth between the two treatments. In addition, jengkol peel POC was proven to be effective in suppressing weed growth around the plants due to the content of allelopathic compounds such as tannins, saponins, and alkaloids. These findings indicate that jengkol peel waste has great potential as a raw material for liquid organic fertilizer that is environmentally friendly, economically valuable, and supports sustainable agriculture